Pengaruh Resistance Band terhadap Ketepatan Shooting Pemain Putri Ekstrakurikuler Futsal SMAN 1 Mayong Kabupaten Jepara - Rizki, Alfian Muhammad; Abdulaziz, Moch. Fahmi (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the use of resistance bands in futsal training, particularly concerning shooting accuracy among female high school players, despite the critical importance of mastering accurate shooting techniques to support team performance. The aim of this study is to measure the effect of resistance band training on the shooting accuracy of female futsal extracurricular players at SMAN 1 Mayong, Jepara Regency. A quantitative method with an experimental approach was used, employing a one-group pretest-posttest design. The sample consisted of 16 female futsal extracurricular members selected through purposive sampling. Data were collected through shooting skill tests conducted before and after the treatment, using an instrument that assessed accuracy scores from four shots. Data analysis was performed using the paired sample t-test with the help of SPSS software. The results show a significant increase in shooting accuracy scores following resistance band training, indicating a positive effect on shot precision. These findings support the theory that resistance training is an effective method for improving lower limb strength and movement precision. The main conclusion of this study is that the use of resistance bands in futsal training programs can significantly enhance shooting accuracy among female players. The implications of this research include theoretical contributions to the literature on physical training in futsal, as well as practical recommendations for coaches and physical education teachers in designing more effective training methods to improve shooting technique performance. This study also opens opportunities for further research on resistance band training variations for other futsal skills.